1990
DOI: 10.1111/j.1365-2125.1990.tb03796.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of cyclosporine concentration in relation to its therapeutic effect and toxicity after renal transplantation.

Abstract: 1. Cyclosporine (CsA) concentrations in plasma and whole blood were monitored prospectively in 66 consecutive kidney transplant recipients for 6 months after transplantation or until graft loss. Immunosuppression was based on treatment with CsA and prednisolone in 27 patients and CsA, azathioprine and prednisolone in 39 patients. 2. Whole blood and plasma samples (separated at 37 degrees C) were collected 10‐12 h after CsA dosage twice weekly over the first 3 months and thereafter once weekly. CsA concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…(5, 17, 19, 25, 51, 52) Every increase in tacrolimus trough by 1 ng/mL increased the hazard of early nephrotoxicity by 22% (p=1.0×10 −31 ) even after adjusting for clinical factors. Every increase in cyclosporine trough by 100 ng/mL increased the hazard by 59% (p=1.8×10 −6 ) after adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…(5, 17, 19, 25, 51, 52) Every increase in tacrolimus trough by 1 ng/mL increased the hazard of early nephrotoxicity by 22% (p=1.0×10 −31 ) even after adjusting for clinical factors. Every increase in cyclosporine trough by 100 ng/mL increased the hazard by 59% (p=1.8×10 −6 ) after adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Nephrotoxicity of cyclosporine is roughly correlated with its blood concentrations (10,11). Animal studies us ing rats have shown that serum creatinine elevates dose dependently during chronic treatment with FK 506 (3).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of cyclosporin A into clinical use in the early 1980s and the development of newer immunosuppressive drugs have led to a significant reduction in acute rejection rates and improvement in shortterm allograft survival (8,35). However, further improvements in immunosuppressive therapy are much needed, because rejection, infection, and drug toxicity remain to be the most common causes of morbidity and mortality in the cardiac transplant population (6, 7, 36 -38).…”
Section: Discussionmentioning
confidence: 98%
“…Since the nonspecific immunosuppression brought by conventional immunosuppressive agents always results in the increased risk of infections and tumors arising from global suppression on the immune system (6,7,35,38). The status of immune condition impacted by LLDT-8 on allograft recipients was much considered.…”
Section: Discussionmentioning
confidence: 99%